Treatment of palm oil mill effluent final discharge using napier grass wetland system - Aziz Ujang, Nor Farhana (2020)
Palm oil mill effluent (POME) is the one of most difficult waste to manage since it is being generated in a large volume most of the time. Treated POME (POME final discharge, POME FD) usually will be discharged to a nearby land or river since it is the easiest and cheapest method to disposal. However, it is common to find that POME final discharge quality does not meet the standard A discharge limit, resulted in unintended pollution towards the rivers. This study has two objectives. The first objective is to determine the effectiveness of constructed wetland system incorporated with the Napier grass to treat POME FD to standard A discharge limit. Second objective is to relate the bacterial community in the constructed wetland system after the treatment of POME FD to physicochemical properties in the effluent of the constructed wetland system. In order to reduce the pollutants level, a modified constructed wetland system with Pennisteum purpureum (Napier grass) as phytoremediation agent was introduced in this treatment process. This system is expected to reduce the contaminant in the POME FD to the standard A discharge limit. In this system, Napier grass was chosen due to its fast, rapid regrowth rates and strong responds to nutrient supply. The wetland system was designed to have a combination of 3 layers of soil, sand and rocks. The reason for this combination is to achieve different removal and performance since stone or gravel at the bottom layer served as the supporting layer, coarse sand used in the second layer was main substrate layer. Meanwhile, fine sand at the upper layer was used to facilitate the dispersion of wastewater and growth of plants. From this study, COD, TSS, colour, and ammonia nitrogen were removed by 51.61%, 91.44%, 72.72% and 63.09%, respectively. With this removal, the wastewater successfully achieved standard A limit set by DOE. Reduction of trace elements in POME FD resulting in the better growth of Napier grass in the treatment system. Trace elements such as silica, caesium, rubidium, strontium, magnesium, manganese and copper reduced by 80.51%, 71.17, 66.07%, 35.56%, 56.81%, 20.81% and 59.27%. Napier grass also managed to reduce the nutrient (macro-nutrient) in the POME FD, such as total nitrogen, phosphorous, potassium and sodium by 54.6%, 91.8%, 75% and 58.46% respectively. From microbial analysis, Anaerolineaceae uncultured, Cyanobacteria norank, Acidobacteria norank and Nitrosomonadaceae uncultured were detected in the samples of POME FD and treated POME FD. Anaerolineaceae uncultured increased from 0.67% to 13.21%. Cyanobacteria norank also shows the increment in the CWs. It increased up to 93.9% in the CWs. At the beginning of this experiment, Acidobacteria norank shows only 0.06%, but after 102 day, the population of Acidobacteria norank increased to 2.44% that give total 97.54% increment. Lastly is Nitrosomonadaceae uncultured. This genus increased from 0.07% to 1.1% and this increment showed a strong prove that nitrification process has occur in the CWs that lead to the decrement of ammonia nitrogen and total nitrogen inside POME FD. As the conclusion, CWs can be used as a treatment method for POME FD since the system is capable to reduce the pollutants level in POME FD down to standard A discharge limit. On the other hand, this research also found that the shift of bacteria from Nitrosomonadaceae genus might be supporting the phytoremediation.